PEMBERIAN KOMUNIKASI, INFORMASI, EDUKASI (KIE) DENGAN MOTIVASI IBU DIDALAM MELAKUKAN MOBILISASI DINI POST SECTIO CAESAREA - Jayanti Imansari; Rita Yulifah; Ardi Panggayuh (Poltekkes Kemenkes Malang, 2019)
Information, Education and Communication or IEC are really important to be given to post sectio caesarea mothers to facilitate them in recovering from the surgery and foster their motivation in doing early mobilization. This study aimed at determining the correlation between the delivery of IEC and mother motivation in performing the early mobilization of post sectio caesarea at Melati Husada Motherhood Woman and Child Care Hospital of Malang. The research design used was quasi experimental with one group pretest posttest approach, with 30 mothers were selected as the samples through consecutive sampling technique.The instrument used in this research was questionnaire. The result of statistical test of Wilcoxon Signed Rank Test, so that it could be concluded that there was a relationship between the delivery of Information, Education and Communication or IEC and mother motivation in carrying out the early mobilization of post sectio caesarea at Melati Husada Motherhood Woman and Child Care Hospital of Malang. Therefore, it is expected that the health workers, especially midwives should put their attention more to the delivery of IEC which fits the appropriate SOP as the supportive care in empowering post sectio caesarea mothers.